2004
DOI: 10.1038/sj.onc.1208330
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of survivin expression and apoptosis by vitamin D3 compounds in two isogenic MCF-7 breast cancer cell sublines

Abstract: Although both the antiapoptotic function of survivin and vitamin D 3 (VD3)-mediated cell growth inhibition and apoptosis have been extensively studied, it is not known whether survivin plays a role in VD3 compound-mediated cell growth inhibition and apoptosis induction. Using an isogenic model of MCF-7 breast adenocarcinoma cells (MCF-7E and MCF-7L sublines that are sensitive and resistant to VD3 compounds), we found that VD3 compounds effectively downregulated survivin in VD3-sensitive MCF-7E cells, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 56 publications
3
45
0
Order By: Relevance
“…However, it has been shown that expression of survivin is critical for CD34+ hemotopoitic cells to go into cell cycle from G 0 -G 1 to S and G 2 -M phases (46,47). Moreover, down-regulation of survivin by vitamin D compounds has been shown to be essential for vitamin D3 -induced G 1 -G 0 cell arrest (42). Additionally, it has been also shown that up-regulation of survivin by Taxol is independent from Taxol-mediated Research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that expression of survivin is critical for CD34+ hemotopoitic cells to go into cell cycle from G 0 -G 1 to S and G 2 -M phases (46,47). Moreover, down-regulation of survivin by vitamin D compounds has been shown to be essential for vitamin D3 -induced G 1 -G 0 cell arrest (42). Additionally, it has been also shown that up-regulation of survivin by Taxol is independent from Taxol-mediated Research.…”
Section: Discussionmentioning
confidence: 99%
“…A scramble sequence (5 ¶-CAGUCGCGUUUG-CGACUGGTT) and reverse chain (5 ¶-CCAGUCGCAAAC-GCGACUGTT) was not present in mammalian cells by BLAST search at National Center for Biotechnology Information. The effectiveness of the survivin small interfering RNA on survivin inhibition was 75% to 90% and confirmed in HeLa cells and MCF-7 cells (42). One day before transfection, 3 Â 10 5 cells were seeded in six-well plate.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…This may be due to inactivation of retinoblastoma or p53 in HeLa cells (98) or selective expression of survivin during mitosis in cancer cells. However, survivin expression in Ki-67-negative breast cancer cells (3), retinoblastoma phosphorylation by survivin resulting from its interaction with Cdk4/p16 INK4a and activation of Cdk2/cyclin E complex in hepatoma cells (12), and resistance to vitamin D -mediated G 1 arrest associated with increased S + G 2 -M phase by ectopic survivin in MCF7 breast cancer cells (14) suggest that survivin may also regulate G 1 -S transition in some cancer cells.…”
Section: Differences In Survivin Expression and Function Between Cancmentioning
confidence: 99%
“…Survivin disruption in HeLa cells induces aberrant mitosis and polyploidy (5) and homozygous survivin deletion in mice results in early embryonic death from disrupted microtubule formation and polyploidy (6), showing a role for survivin in cell division. Although survivin expression is associated with cell cycle progression and regulation of mitosis in most transformed cell systems investigated (1 -3, 7), it also regulates G 1 -S transition in T lymphocytes (8,9), normal hematopoietic progenitor cells (10,11), hepatoma cells (12,13), and breast cancer cells (14).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of epidermal growth factor receptor (EGFR) expression by 1,25(OH) 2 D 3 is also thought to aid cell growth inhibition (McGaffin & Chrysogelos 2005, Belochitski et al 2007 as well as the downregulation of survivin, an inhibitor of apoptosis (Li et al 2005, Koike et al 2011) and platelet-derived growth factor downregulation by 1,25(OH) 2 D 3 . A study with CRC cells suggests that 1,25(OH) 2 D 3 -mediated antiproliferative effects are dependent on the dual role of the VDR: first, as a transcriptional factor and secondly, as a nongenomic activator of the Rho-ROCK-p38MAPK-MSK signaling pathway (Ordonez-Moran et al 2008).…”
Section: Introductionmentioning
confidence: 99%